Philosophy 167: Class 5 - Part 10 - Galileo's Trial: The Sentencing, and Galileo's Abjuration. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Discusses the sentencing of Galileo for heresy, and his abjuration.; Opening line: "At any rate, let's look at the trial for the moment."; Duration: 7:24 minutes.; Segment: Class 5, Part 10.